Exploring radio promotions in Singapore : an audio production (Mandarin). - Koh, Mui Sang. (2009)
Radio is a personal and immediate medium. Its accessibility and portability nature also facilitates multi-tasking, a boon for many busy urbanites. With its growing market share in Singapore which has tripled since 1990, radio has proven to be an effective means of communicating to the consumer. In the face of rising radio competition where ratings mean everything, it is increasingly important to promote one’s station to attract first listeners, then advertisers. As a result, radio promotion, or the art of selling one’s radio station, is gaining emphasis. The audio production to be featured is an exploratory piece on radio promotion as practised in Singapore.